Influence of Return on Equity (ROE) and Debt Equity Ratio (DER) On Company Value and Share Prices - Ramadhani Salsabila, Rima; Triyonowati, Triyonowati; Suhermin, Suhermin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aimed to examine and analyze the effect of Return On Equity (ROE) and Debt to Equity Ratio (DER) on firm value and the stock price in Real Estate and Property; through annual financial statements and the company's performance that were listed on the Investment Gallery of Indonesia Stock Exchange, STIESIA. Besides, it aims to examine and analyze the effect of Return On Equity and Debt to Equity Ratio on stock prices either directly or indirectly, through firm value. Since firm value was a mediating variable, it could measure the company's performance that was reflected in stock price. Furthermore, the population was 49 companies that were listed on the Gallery of Indonesia Stock Exchange, STIESIA during 2015-2021. The data collection technique used purposive sampling. In line with that, there were 11 Real Estate and Property companies as the sample. Additionally, the data analysis technique used multiple linear regression with path analysis and causal step, as well as SPSS (Statistical Product and Service Solutions). As a result, it is concluded that ROE and DER have a significant effect on firm value. Likewise, the firm value had a significant effect on the stock price. Both ROE and DER have an insignificant effect on the stock price. While DER could increase the risk for stakeholders. In other words, the higher the DER was, the lower the stock price (undervalued) would be. As a result, the stock won't interest the stakeholders. On the other hand, the firm value may not be the mediating variable of ROE on the stock price. However, the firm value could mediate DER on stock price (full mediation). In conclusion, Debt to Equity Ratio (DER) could encourage the stakeholders to invest their stocks in Real and Property companies.